2016
DOI: 10.4310/joc.2016.v7.n1.a4
|View full text |Cite
|
Sign up to set email alerts
|

The adjoint representation of a classical Lie algebra and the support of Kostant’s weight multiplicity formula

Abstract: Even though weight multiplicity formulas, such as Kostant's formula, exist their computational use is extremely cumbersome. In fact, even in cases when the multiplicity is well understood, the number of terms considered in Kostant's formula is factorial in the rank of the Lie algebra and the value of the partition function is unknown. In this paper we address the difficult question: What are the contributing terms to the multiplicity of the zero weight in the adjoint representation of a finite dimensional Lie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
14
0
2
Order By: Relevance
“…Notice that this element will also have simple reflections appended to it as i increases and eventually reaches this element. This process is guaranteed to work because we know that once the expression σ(λ + ρ) − (µ + ρ) yields a negative coefficient when expressed as a sum of simple roots, appending more reflections to σ which make the length of σ increase will only decrease the coefficients of the simple roots further, as was proven by the first and second author in [18,Proposition 3.4]. We present this result below, but omit its proof as it is both technical and lengthy.…”
Section: Generating the Weyl Alternation Setmentioning
confidence: 96%
See 2 more Smart Citations
“…Notice that this element will also have simple reflections appended to it as i increases and eventually reaches this element. This process is guaranteed to work because we know that once the expression σ(λ + ρ) − (µ + ρ) yields a negative coefficient when expressed as a sum of simple roots, appending more reflections to σ which make the length of σ increase will only decrease the coefficients of the simple roots further, as was proven by the first and second author in [18,Proposition 3.4]. We present this result below, but omit its proof as it is both technical and lengthy.…”
Section: Generating the Weyl Alternation Setmentioning
confidence: 96%
“…For example, Harris showed that the number of Weyl group elements contributing nontrivially to the multiplicity of the zero weight in the adjoint representation (the representation with highest weight equal to the highest root) of slr+1(C) was given by Fibonacci numbers [16]. Later, Harris, Insko, and Williams, generalized these results to show that the number of Weyl group elements contributing nontrivially to the multiplicity of the zero weight in the adjoint representation of all classical Lie algebras is governed by linear homogeneous recurrence relations with constants coefficients [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This formula is an impractically large sum over the elements of the corresponding Weyl group. For the classical Lie algebras, Pamela [3] and her collaborators [4] determined that the vast majority of the terms in this sum vanish, and they enumerated the contributing terms; these are rather unexpected results on a central object in mathematics.…”
Section: Ricardo Cortez Is the Pendergraft William Larkin Duren Profesmentioning
confidence: 99%
“…This is due to the fact that in general the number of terms appearing in the sum are factorial in the rank of the Lie algebra and there is no known closed formula for the partition function involved. There has been recent progress in addressing these complications for particular weight multiplicity computations [4,5,7,8].…”
Section: Introductionmentioning
confidence: 99%